Uji Aktivitas Antioksidan dari Formulasi Sabun Mandi Cair Ekstrak Etanol Biji Kopi Robusta (Coffea canephora) - Achmad Saehu; Nani Suryani; Fajrin Noviyanto (Universitas Cokroaminoto Palopo, 2022)
Soap is one of cosmetic products whose purpose is to cleanse the body of soiled. Several cosmetic products were added antioxidant to protect skin from free radical that caused skin damage such as aging. Robusta coffee beans (Coffea canephora) contain bioactive phenolic compounds such as fenolic acid, chlorogenic acid and caffeic acid that have antioxidant, also have an aromatic distinctive odor. Any research mention that antioxidant activities of unroasted robusta coffee beans have value of IC50 0,131 (mg/ml), while other research mention that robusta coffe bean have value of IC50 140,24 ppm and classified as moderate antioxidant according to Blois criteria. The benefits of the coffee can be used as an active ingredient in liquid soap. The aim of this study to determine the formula of ethanol extract Robusta (Coffea canephora) liquid soap and antioxidant activities test. Liquid soap is made in four formulations with variation of coffee extract 0%; 0,014%; 0,14%; and 1,4 % and with test criteria physical properties, pH and free alkali test compared with the standard quality of liquid soap SNI 06-4085. Antioxidant activities test were used DPPH method with spectrophotometry uv-vis with 515 nm wave length. The absorbance of DPPH solutions before and after addition the sample was calculated as percent (%) of inhibition. Then the percent of inhibition value is entered into linear regression equation until the IC50 value is obtained. The result of the phytochemical test of coffee bean exstract contain alkaloid compounds which are antioxidants. Physical test, pH and free alkali did not meet all SNI quality standards, as well as antioxidant acticity test which gave IC50 values above 200, which means they have no antioxidant acticity. Therefore, in further research, it is necessary to optimized the formulation